Early Life Stress and Chronobiological Rhythms Desynchronization: Possible Impact on Mood Symptoms and Suicidal Ideation in Bipolar Disorder. Issue 7 (July 2021) - Caruso, Danila; Palagini, Laura; Miniati, Mario; Massa, Lucia; Marazziti, Donatella; Geoffroy, Pierre Alexis; Etain, Bruno
Abstract : Abstract: The study aimed at investigating the potential impact of early stressful events on the clinical manifestations of bipolar disorder (BD). A sample of 162 adult individuals with BD was assessed using the Structural Clinical Interview for DSM-5, the Beck Depression Inventory-II, the Young Mania Rating Scale, the Early Trauma Inventory Self Report-Short Form, the Biological Rhythms Interview of Assessment in Neuropsychiatry, the Insomnia Severity Index, and the Scale for Suicide Ideation. A significant path coefficient indicated a direct effect of early life stressors on biological rhythms (coeff. = 0.26; p < 0.001) and of biological rhythms on depressive symptoms (coeff. = 0.5; p < 0.001), suicidal risk (coeff. = 0.3; p < 0.001), and insomnia (coeff. = 0.34; p < 0.001). Data suggested that the desynchronization of chronobiological rhythms might be one mediator of the association between early life stress and the severity of mood symptoms/suicidal ideation in BD. Addressing circadian rhythm alterations in subjects exposed to early stressors would help in preventing consequences of those stressors on BD.